Synthesis of resource conservation networks with p-graph approach—Direct reuse/recycle - Lim, C, H. (Animo Repository, 2017)
The need for climate change adaptation in industry has led to intensified research in industrial resource conservation, as well as waste reduction, to enable sustainable operations to be achieved even under conditions of declining water resources. Such sustainability initiatives can be facilitated using the systematic approach of process integration (PI). Of particular interest are resource conservation network (RCN) problems, which have been solved using pinch analysis or mathematical programming methods. On the other hand, other process system engineering (PSE) tools such as the process graph (or P-graph) framework offers potential alternative approaches to RCN problems. To date, P-graph methodology has been used for various process network synthesis (PNS) problems; however, no RCN synthesis applications have been reported thus far. This paper presents a novel implementation of P-graph for RCN synthesis. In addition to the inherent computational efficiency of its algorithms, P-graph allows the elucidation of optimal and near-optimal solutions, a feature which is potentially useful for practical decision-making. Capital and operating cost considerations can be incorporated easily. In this paper, direct reuse/recycle scheme is applied for in-plant RCN and inter-plant RCN (IPRCN). © 2017, Springer Science+Business Media Singapore.